Pengaruh Bimbingan Kelompok Teknik Pelukan Kupu-Kupu terhadap Kecemasan menghadapi Ujian Akhir Semester - Muhammad Arif Hidayatullah; Agus Wibowo; Hadi Pranoto (Counseling Milenial (CM), 2025)
Education must be prepared in such a way that it is able to answer all the problems and challenges of life in the future for students. The end of the semester determines whether the student will graduate or not. In this study the goal to be achieved is to test the butterfly hug technique in influencing students to overcome the problem of excessive self-anxiety. In this study, researchers will use a quantitative approach, namely a research approach where research data is sought in the form of numbers and analyzed using statistics. research population can be concluded as research objects that can be obtained from the information in question. This research is a population of students at SMP Negeri 07 Mesuji Timur. Data analysis is a systematic process of synthesizing data obtained from interviews. Based on the results of the research that has been done, the anxiety of students at SMPN7 Mesuji in facing their final semester exams was initially in the high category. Then to overcome these problems in this study the researchers tried to apply services with the butterfly hug technique in the hope of reducing and improving initial conditions that are easily anxious to be more calm and confident